Introduction to Medical Microbiology: A Hands-on Laboratory - Melphine Harriott (Association of American Medical Colleges, 2013)
Abstract Introduction While anatomy laboratory sessions remain a staple in the medical school curriculum, microbiology laboratories are often phased out for virtual labs or phased out completely. This basic hands-on laboratory introduces medical students to medical microbiology and provides an overview of the multistep process of pathogen identification. Methods During this laboratory, students work in groups to rotate through stations that cover basic microbiology media, gram stains, normal flora, biochemical identification, and susceptibility testing. Some of the stations are case-based; students review gram stains, perform basic tests, and then use flow charts to identify the pathogen. Results This introductory laboratory was the first microbiology laboratory in our integrated organ system curriculum and occurred within the first semester of the first year. It was successfully implemented with 75 students and was well received by the students. Discussion Microbiology laboratories, such as the one presented here, can assist students to visualize and reinforce the material learned in lecture session and provide them with an overview of the multistep process of pathogen identification.